How can urban resilience manage the Wadi floods: Case of Oued El Harrach in Algiers - Manel SOUIDI; DAGHMOUM Haithem Amine; Rahima HADIDI (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The safety of people and ecosystems is seriously threatened by severe weather events and natural catastrophes. To guarantee that every community benefits from a safe, sustainable built environment, social and economic factors must be considered in resilient urban planning.  The commune (municipality) of El Harrach is situated in the east of Algiers and traversed by the same-named river. With growing urbanization throughout the years, El Harrach is strategically located overlooking the Bay of Algiers. However, a number of threats persist, such as the chemical pollution and the risk of flooding. Through this study, we will explore the advantages and limits of urban resilience against the risk of flooding in El Harrach region using a combination of two urban analysis methods: SWOT (for the risk analysis) and NBS (for the proposed alternatives). The results will also be presented in the form of GIS maps in order to suggest future decision-making in the land use regional plan framework.